Instantaneous method of detecting ionospheric disturbance. Issue 5 (1st May 2019) - Hou, Chengyu; Fu, Shanyin; Gao, Qingfeng; Chen, Di; Yang, Lin
Abstract : High‐frequency skywave radar signals propagating through the ionosphere are often affected by travelling ionosphere disturbances (TIDs) which modulate the signal phase and frequency. This obscures slow moving targets. Conventionally, ionospheric contamination is detected by comparing Doppler spectra with different coherent integration times (CITs). However, this approach requires sometimes unacceptable observation time. In this study, the authors propose an alternative and simple, real‐time method which utilises the high‐order instantaneous moment (HIM) and high‐order ambiguous function (HAF) of the echo signal. Their proposed algorithm uses symmetry of the peak structure of HIM and the stationarity of HAF to instantaneously detect contamination of echo signal. The effectiveness and instantaneity of the algorithm in detecting TIDs are demonstrated by comparing the traditional MultiCIT method. The processing time for both methods is of the same order of milliseconds, but the observation time for the new method is half of that for MultiCIT.